2019
DOI: 10.29252/jhehp.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation of the Health Literacy Questionnaire (HLQ) in Shahrekord Cohort Study, Iran

Abstract: In addition, health literacy refers to the degree of the ability to obtain, communicate, accept, and understand health information and services, which enables individuals to make health-related decisions [4]. Health literacy is a predictor of health outcomes and healthcare utilization [5]. Low health literacy is associated with the less frequent use of preventative measures, inability to communicate with healthcare professionals, low adherence to recommended Journal of Human, Environment, and Health Promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The result of this study is consistent with previous work that found the HLQ to have good measurement properties with robust construct validity and reliability for each of its nine Domains ( Ahmadi & Salehi, 2019 ; Huang et al, 2019 ; Kolarcik et al, 2017 ; Maindal et al, 2016 ; Morris et al, 2017 ; Nolte et al, 2017 ; Osborne et al, 2013 ; Richtering et al, 2017 ). This indicates that the nine HLQ domains each consistently measure a single HL construct and together they provide reliable and valid information on nine distinct HL constructs.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The result of this study is consistent with previous work that found the HLQ to have good measurement properties with robust construct validity and reliability for each of its nine Domains ( Ahmadi & Salehi, 2019 ; Huang et al, 2019 ; Kolarcik et al, 2017 ; Maindal et al, 2016 ; Morris et al, 2017 ; Nolte et al, 2017 ; Osborne et al, 2013 ; Richtering et al, 2017 ). This indicates that the nine HLQ domains each consistently measure a single HL construct and together they provide reliable and valid information on nine distinct HL constructs.…”
Section: Discussionsupporting
confidence: 90%
“…We have shown that the HLQ can be used to measure HL in online health educational platforms. This adds to the existing knowledge on the validated modes of delivery for HL measurements such as self-administered paper-based, online/web-based, face-to-face, and telephone-based interviews that have been explored in different settings and populations ( Ahmadi & Salehi, 2019 ; Debussche et al, 2018 ; Huang et al, 2019 ; Jessup et al, 2017 ; Kolarcik et al, 2017 ; Maindal et al, 2016 ; Morris et al, 2017 ; Mullan et al, 2017 ; Nolte et al, 2017 ; Rademakers et al, 2020 ; Richtering et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tools were used for baseline data collection from 2015 to 2019 and are described in Table 1 . In addition to the extensive standard PERSIAN questionnaires, additional questionnaires unique to SCS were also completed, including General Health [ 22 ], WHO Quality of Life-BREF [ 23 ], Chronic Stressors and Coping Strategies [ 24 ], WHO MONICA and the ROSE Angina questionnaire [ 25 ], Social Capital [ 26 ], Screening Tool for Joint Pain and Musculoskeletal Diseases [ 27 ], Health Literacy [ 28 ], Oxford Happiness [ 29 ], and Oswestry Low Back Pain Disability [ 30 ], following SCS protocols [ 18 ] in CH&B (Table 1 ) and additional data unique to SCS were also completed including body composition variables included total body water, body fat mass and percentage, and muscle thickness, which were measured using a body composition analyzer (Tanita, Japan). A spirometry test (pulmonary function test) was performed using the Spirometer device (Spirolab [MIR, Italy)].…”
Section: Methodsmentioning
confidence: 99%